Effect of Additive Type and Concentration on the Physicochemical Stability of Aloe vera Gel-Based Edible Coating - Ni Luh Putu Sulis Dewi Damayanti; Luh Suriati; Ni Kadek Desy Andya; Yeo Vinco (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Aloe vera gel has attracted considerable attention as a natural edible coating material due to its polysaccharide-rich composition and environmentally friendly characteristics. However, its application is limited by poor physicochemical stability during storage, including changes in pH, viscosity, color, brightness, and transparency. This study aimed to evaluate the effect of additive type and concentration on the physicochemical stability of Aloe vera gel-based nano-edible coatings during storage. The experiment was conducted using a completely randomized design with four additive treatments, namely citric acid, ascorbic acid, potassium sorbate, and mixed additives, each applied at concentrations of 0.15%, 0.30%, and 0.45%. The formulated gels were stored under refrigerated conditions, and changes in pH, viscosity, total color difference (?E), brightness (L*), and transparency were periodically evaluated. The results showed that the type and concentration of the additive significantly affected the stability of Aloe vera gel. Citric acid and ascorbic acid were more effective in maintaining pH stability, brightness, and colour retention, while potassium sorbate mainly contributed to microbial stability but had limited effects on optical properties. Mixed additive formulations, particularly at lower concentrations, demonstrated synergistic effects by improving overall physicochemical and visual stability during storage. These findings indicate that appropriate selection and optimization of additives are essential for developing stable Aloe vera gel-based nano-edible coatings suitable for postharvest and food preservation applications. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production